2023
DOI: 10.3390/foods12061262
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Sausages Using Pork and Cricket Flour: Texture and Oxidative Storage Stability

Abstract: This study aimed to study the functionalities of cricket flour (CF) and the effects of the addition of CF on the texture and oxidative stability of hybrid sausages made from lean pork and CF. Functional properties of CF, including protein solubility, water-holding capacity, and gelling capacity, were examined at different pHs, NaCl concentrations, and CF contents in laboratory tests. The protein solubility of CF was significantly affected by pH, being at its lowest at pH 5 (within the range 2–10), and the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…All treatments added with EIP showed lower PV values but higher TBARS values than those of PC and NC (p<0.05). Han et al (2023) reported that the TBARS value of hybrid sausage added with cricket flour increased. Also, it has been reported that adding silkworm pupae flours to emulsion sausage increases the TBARS value ( Kim et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…All treatments added with EIP showed lower PV values but higher TBARS values than those of PC and NC (p<0.05). Han et al (2023) reported that the TBARS value of hybrid sausage added with cricket flour increased. Also, it has been reported that adding silkworm pupae flours to emulsion sausage increases the TBARS value ( Kim et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%